Tools for Providing Technologies to Solve Organizational Management Problems - B. N. Gerasimov; K. B. Gerasimov (Управленческие науки)
Subject. The diversity and significance of existing different economic systems cannot be overestimated. Therefore, it is obvious that they need to be investigated, adapted, designed and used.Purpose. The purpose of this paper is to present the results of a search study in the field of modern organizations management tools. The quality and effectiveness of managerial activity is currently determined not so much by the paradigms, concepts or principles used, but rather by the forms and content of the elements of the process activity used, and by the level of performance of professional managerial tasks.Methodology. The research consisted in the analysis of modern developments in the field of business process management in socio-economic systems. Materials on structuring and classification of management activity from various points of view were used. A study and review of various means and methods of management wascarried out. The most common structural unit of management activity in practice and in many scientific works is the task, which is a complex of procedures for converting input information into output information, performed at a certain time with a given quality. Among the implementation tools, the methods of performing the procedures, the methods of making managerial decisions and the elements of management were chosen.Results. The instrumental support of solving the tasks of the subprocess management of the development of managers of the organization was accomplished. Their composition is determined, the characteristic is given and features of their application are considered. It was shown the distribution of management tools for the tasks of the subprocess management of the development of managers of the organization. Practical implementation of tools to provide technologies for the application of management tasks in the organization is shown.Conclusions. The research is valuable for teachers, managers and consultants who conduct training, retraining and development of the professional competence of managers in organizations of any profile, taking into account industry specificity. Thus, the use of management technology tools allows to improve the quality and efficiency of the activities of a modern organization.